A pilot study of a long acting somatostatin analogue for the treatment of refractory rheumatoid arthritis. Issue 9 (1st September 2001) - Paran, D; Elkayam, O; Mayo, A; Paran, H; Amit, M; Yaron, M; Caspi, D
Abstract : OBJECTIVE: To evaluate the efficacy and safety of a long acting somatostatin analogue in a subset of patients with refractory rheumatoid arthritis (RA). METHODS: Ten patients with active, refractory RA, who had failed to respond to at least four disease modifying antirheumatic drugs (DMARDs), were treated with monthly intramuscular injections of 20 mg of a long acting preparation of octreotide (Sandostatin-LAR) for three months. They were evaluated every two weeks in an open label pilot study. The primary measure of clinical response was the American College of Rheumatology criteria for a 20% improvement in measures of disease activity (ACR 20). RESULTS: Eight patients completed the 14 week trial, while two patients received only one or two doses of the somatostatin analogue, but were eligible for evaluation. On an intention to treat basis 6/10 patients responded: four patients met the ACR 20 criteria at weeks 6–10, while two patients continued to improve with time, and met the ACR 50 and 70 criteria respectively, at week 14. On evaluation of the 10 patients as a group, a significant improvement (p<0.05) was noted in the mean visual analogue scales of pain, doctor's and patient's global assessment of disease activity, and in the mean number of swollen joints. Adverse effects were minor: transient bloating and loose stools, an urticarial rash (n=1), and a transient increase of liver enzymes (n=1). CONCLUSION: Treatment with a long acting somatostatin analogue led to significant clinical improvement in a subset of patients with active, refractory RA. The treatment was relatively safe and well tolerated. Further large, placebo controlled studies are required to evaluate this drug as a potential DMARD for patients with RA.